Effect of Herbal Feed Additives on Performance, Immunity, Serum Parameters and E. coli Counts of Broilers under Heat Stress - Rao, Hanumanth (Indian Journal of Animal Nutrition, 2021)
The present experiment was conducted to investigate the effect of different herbal preparations on the performance of broilers. A total of 250 day-old male broiler chicks were randomly divided into five treatment groups with ten replicates of five birds each. The experimental design consisted of; T1: control diet, T2: Herbal powder I (containing Withania somnifera, Phyllanthus emblica, Glycrrhiza glabra, Tribulus terrestris and Asparagas racemosus), T3: Herbal powder II (containing Withania somnifera, Ocimum sanctum, Mangifera indica and Shilajit), T4: Herbal powder III (Ayuce herbal powder), T5: Vitamin E (70 mg per kg) and Se (0.15 mg per kg). The results indicated that supplementation of herbal preparations (T2, T3 and T4), and vitamin E and Se significantly (P